Isolation and characterization of chromium resistant Enterobacter aerogenes from marine soil - Gomes, Shaikat Marcel (BRAC Univeristy, 2017)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2016.